2014
DOI: 10.20883/medical.e80
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist’s role in the system of palliative and hospice care in Ukraine and Poland

Abstract: Introduction. The efficient pharmacotherapy is an important part of palliative and hospice care, and requires a multidisciplinary approach to the patients. The pharmacist, as the member of the multidisciplinary therapeutic team, is responsible for performing pharmaceutical care, which provides safe and efficient treatment. The aim of the research was to conduct a comparative research about the status of palliative and hospice care and role of the pharmacist (clinical pharmacist) in Ukraine and Poland.Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…A survey of Polish hospices found that HPhs provided regular medicines advice to the MDT and organised medicines supply (in most of the 57% of hospices which had pharmacist input) although there was very little patient contact 12 . A similar study in Ukraine found that there was no current role for HPhs within the palliative care team although many doctors thought that there should be 13 . A multi-centre survey across Canada and Australia found that most hospices surveyed employed pharmacists and they were important members of the MDT with the most common duty reported as discharge medication review 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A survey of Polish hospices found that HPhs provided regular medicines advice to the MDT and organised medicines supply (in most of the 57% of hospices which had pharmacist input) although there was very little patient contact 12 . A similar study in Ukraine found that there was no current role for HPhs within the palliative care team although many doctors thought that there should be 13 . A multi-centre survey across Canada and Australia found that most hospices surveyed employed pharmacists and they were important members of the MDT with the most common duty reported as discharge medication review 14 .…”
Section: Introductionmentioning
confidence: 99%
“…HPs had often developed methods of regular and ad-hoc communication with members of the MDT (depending on how much time they had) to pass-on or receive relevant information. The provision of information to the MDT was found to be commonplace as has been found elsewhere [16][17][18][19]. Lack of full access to patient records leads to time wasted piecing together information from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges were shown in communication, knowledge, sourcing medicines and general time pressures with most HPs working part-time. This is the first study to qualitatively explore the role of a HP, although some surveys have been conducted concerning duties, hours and MDT working [ 6 , 17 19 ]. Our main findings concur with a previous study in 1995 of HPs performing administrative, clinical, educational and supply however the role of the pharmacist now encompasses much more in terms of clinical duties than was expected 25 years ago [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations